Gossypiboma. Issue 8 (5th July 2016) - De, Utpal; Dutta, Manas; Chattopadhyay, Prasenjit
Key Clinical Message: Gossypiboma is a dreadful complication and nightmare for a surgeon. It might cost the patient his life and the surgeon his reputation. It is a preventable condition and additional safeguard measures should be sought and implemented to prevent against human error. Abstract : Gossypiboma is a dreadful complication and nightmare for a surgeon. It might cost the patient his life and the surgeon his reputation. It is a preventable condition and additional safeguard measures should be sought and implemented to prevent against human error.